The prophecy and its fate. Austrian conservation ideas after 1918 in South-Eastern Europe - Špikić, Marko (2013)
Presentation on the continuity and discontinuity of theoretical ideas in conservation in the past century, starting with Alois Riegl's and Max Dvorak's ideas. Their survival and revival in 20th century and contemporary Croatia and Central Europe.
Projekt MZOS
ENG